Clinical comparative study on efficacy and safety for treatment of coronary heart disease with cobalt-base alloy bio absorbable polymer sirolimus-eluting stent and PARTNER stent. (12th October 2011) - Li, Zhanquan; Wang, Haichang; Lv, Shuzheng; Liu, Li; Guo, Wenyi; Yuan, Ming; Yan, Hongbin; Zhao, Hanjun; Lang, Suping
Abstract : Objective: To evaluate the efficacy and safety for treatment of coronary heart disease with cobalt-base alloy bio absorbable polymer sirolimus-eluting stent. Methods: A total of 228 patients with up to two de novo native coronary artery lesions (reference vessel diameter, 2.5 to 4.0 mm; target lesion stenosis ≥70%; lesion length ≤40 mm) were randomised 1:1 to cobalt-base alloy bio absorbable polymer sirolimus-eluting stent (CAS) group (n=105) versus PARTNER stent group (n=123). Antiplatelet therapy consisted of aspirin (100 mg/d) and clopidogrel (75 mg/d) ≥12 months. Clinical follow-up was scheduled at 1, 3, 6, 9 and 12 months and angiographic follow-up at 6–9 months. The primary end point is in-stent late loss and in-segment late loss at 6–9 months. Secondary end point is MACE at 12 months, consisting of cardiac death, MI, or ischemia-driven target vessel revascularisation (TVR). Results: Baseline clinical and angiographic characteristics were well matched between two groups except for higher rate of hypertension and NYHCα in PARTNER stent group. Angiographic follow-up was available at 6–9 months in 175 patients (77%). Procedure was successful in all patients. 6–9 months angiographic follow-up indicated that there were no significant differences of in-stent and in-segment late loss between CAS group and PARTNER stent group ((0.34±0.30) mm vs (0.29±0.28) mm, p=0.1968, (0.32±0.34) mm vs (0.29±0.30) mm, p=0.4169]. Clinical follow-up indicated that there were no significant differences of MACE at 12 months between CAS group and PARTNER stent group (5.71% vs 4.07%, p=0.5543). there were no significant differences of TVR at 12 months between CAS group and PARTNER stent group (5.71% vs 4.07%, p=0.5543). There was no cardiac death, MI and in-stent thrombosis in both of two groups during 12 months follow-up. Conclusion: Six to nine months angiographic and 1 year clinical outcome on efficacy and safety were comparable in patients implanted with cobalt-base alloy bio absorbable polymer sirolimus-eluting stents and PARTNER stents.